Specialized bibliography of the central canton of the province of Heredia, Costa Rica, 1824-2003 - Ulate Montero, Jenny (2008)
The bibliographies have been part of the work of people interested in rescuing the documentary heritage of the country, which were made in order to make an inventory of the printed production of the country. With the growth of the documentary production the bibliography takes a new conception, they stop elaborating universal bibliographies due to the difficulty of covering everything published in the world to give way to the national bibliographies and the specialized ones. This research consisted in making a specialized bibliography of the Central Canton of Heredia, taking into account local and national agencies.